Stakeholders’ Trust in Automated Driving - Järvi, Jesse (My University, 2023)
As automated driving continues to evolve, trust plays a pivotal role in its adoption and acceptance in society. This thesis aims to explore different stakeholders’ trust in automated driving systems by examining factors that influence said trust. A questionnaire was developed in order to gather recent data on trust in automated driving systems and it was used to analyze factors that influence trust in automated driving. The questionnaire was also used to identify possible methods that could improve trust. The questionnaire in this thesis also identifies which types of stakeholders would trust automated driving, for example by examining familiarity. Furthermore, the study addresses the issue of vulnerable road users reasons for distrust in automated driving. Identifying these issues in such fields as ethics, legislation, or safety can lead to enhancement of development strategies, which in turn would enhance stakeholders’ trust in automated driving. This thesis provides valuable insights into the relationship between trust, technology adoption, and user apprehensions on automated driving, with a goal of improving the development considerations in the rapidly evolving transportation technology.
Keywords: trust, automated driving, cybersecurity, trust factors, technology adoptation